OSTEOCHONDROMA FRACTURE IN YOUNG ATHLETE: A CASE REPORT - Ilham Abdullah Irsyam; Andriandi Andriandi; Nehemia Meliala (Universitas Airlangga, 2021)
Background: Osteochondroma is a benign bone tumor that most cases are asymptomatic. The symptoms may occur as a complication of osteochondroma, which is rarely happened. Surgical intervention is needed to treat the complications.Case: A 20-year old male football athlete presented with pain on his left thigh's lump after he fell during his training. Mass and tenderness on the medial side of the left distal femur were found. Plain X-Ray showed an irregular mass on the left distal femur's surface with a fracture through the stalk of pedunculated osteochondroma. The patient underwent total excision of the osteochondroma.Discussion: The fracture of the osteochondroma often occurs in teenagers because they are more active physically. It happens due to direct or indirect injury. The treatment of this fracture is controversial between observation or surgical excision. In this case report, the patient could demonstrate full weight-bearing right after the surgery.Conclusion: Fracture as a complication in osteochondroma often happens to teenagers, and surgery proved to give a good outcome in this case.